Indocyanine green guidance improves the efficiency of extended pelvic lymph node dissection during laparoscopic radical prostatectomy. (5th March 2021) - Claps, Francesco; Ramírez‐Backhaus, Miguel; Mir Maresma, Maria Carmen; Gómez‐Ferrer, Álvaro; Mascarós, Juan Manuel; Marenco, Josè; Collado Serra, Argimiro; Casanova Ramón‐Borja, Juan; Calatrava Fons, Ana; Trombetta, Carlo; Rubio‐Briones, Jose
Abstract : Objectives: To evaluate whether indocyanine green guidance can improve the quality of extended pelvic lymph node dissection in patients undergoing radical prostatectomy. Methods: A total of 214 patients underwent laparoscopic radical prostatectomy with indocyanine green‐guided lymph node dissection plus extended pelvic lymph node dissection. These patients (group A) were matched 1:1 for clinical risk groups according to the National Comprehensive Cancer Network classification with patients who underwent the same procedure without fluorescence guidance (group B). Biochemical recurrence was defined as two consecutive prostate‐specific antigen rises of at least 0.2 ng/mL. The Kaplan–Meier method and Cox regression models were used to identify predictors of biochemical recurrence. Results: The median number of retrieved nodes was significantly higher in group A (22 vs 14, P < 0.001). The rate of lymph node metastases was higher in group A (65.9% vs 34.1%, P = 0.01). Increasing the yield of lymph node dissection was independently and negatively correlated with the biochemical recurrence risk in both overall and pN‐positive patients (hazard ratio 0.97, P = 0.03; and hazard ratio 0.95, P = 0.02). The 5‐year biochemical recurrence‐free survival rates were (75.8% vs 65.9, P = 0.09) and (54.1% vs 24.9%, P = 0.023) for group A and group B in the overall cohort and pN‐positive cohort, respectively. Conclusion: Indocyanine green‐guided lymph node dissection plus extended pelvic lymph node dissection improves identification of lymphatic drainage, resulting in a higher number of lymph nodes and retrieved lymph node metastases, and allowing a more accurate local staging and a prolonged biochemical recurrence‐free survival.